Pemberdayaan Ekonomi Masyarakat pada Lingkungan Empat Lorong Mesjid Gang Iman Kelurahan Bagan Deli Belawan Melalui Pengembangan Media Hidroponik - Mardi, Rina Walmiaty; Asmalidar, Asmalidar; Siregar, Indra; Susilawaty, Susilawaty (Politeknik Negeri Pontianak, 2023)
Community Economic Empowerment in the Four Alleys of the Gang Iman Mosque, Bagan Deli Belawan Sub-District through the Development of Hydroponic Media is carried out to assist in increasing the community's income and economy. The container for the results of this hydroponics has been provided by the Community Service Team. Training in management, finance and marketing is also carried out by the Service Team. With this, the community's economic problems will be resolved through the sale of hydroponic plants. Training, mentoring and introduction of suppliers to Partners aims to generate income and make their free time more productive and useful for Partners in the long term. . coupled with the environmental conditions near the coast, there are frequent dead tides and ROB floods and mothers have more unproductive time. Method Approach to the community and discuss with local officials what steps are considered appropriate to solve problems and provide solutions faced by the community. With training, mentoring and supervision of the activities provided to get the right results in empowering the community's economy in the Bagan Deli Belawan environment.